Pendampingan Belajar Siswa dalam Memahami Determinan dan Invers Matriks - Alifia, Shela; Nensi; Sulaestri, Sri; Hardiyanti, Dwi (Faculty of Tarbiyah and Teacher Training, 2025)
Mathematics is an important subject because the topics in it are interrelated at every level. Matrix is one of the subjects where students make many mistakes and have difficulty in understanding concepts, especially determinants and inverses of matrices. This service is a learning assistance for students at MA Madani Alauddin Pao-Pao South Sulawesi, which aims to provide guidance to students in solving determinants an inverse of matrices through determinant an matrix board media. This service was carried out by Mathematics Education students of the Faculty of Tarbiyah and Keguruan UIN Alauddin Makassar for 8 meetings, by making determinant and invers matrix board media to help students understand matrix concepts, especially determinants and inverses of matrices. The result of this service resulted in an increase in students’ understanding of the determinant dan inverse matrix and produced a positive response from students with the enthusiasm shown towards learning assistance.